2021
DOI: 10.1038/s41419-021-03790-w
|View full text |Cite
|
Sign up to set email alerts
|

MYCN mediates TFRC-dependent ferroptosis and reveals vulnerabilities in neuroblastoma

Abstract: MYCN amplification is tightly associated with the poor prognosis of pediatric neuroblastoma (NB). The regulation of NB cell death by MYCN represents an important aspect, as it directly contributes to tumor progression and therapeutic resistance. However, the relationship between MYCN and cell death remains elusive. Ferroptosis is a newly identified cell death mode featured by lipid peroxide accumulation that can be attenuated by GPX4, yet whether and how MYCN regulates ferroptosis are not fully understood. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(72 citation statements)
references
References 44 publications
(48 reference statements)
3
59
0
Order By: Relevance
“…5C, D). To further support these findings, we stained hamster lung tissue sections and observe positive TUNEL staining, consistent with apoptosis, with peak at 7 dpi and increased TFRC (Transferrin Receptor Protein 1), a specific marker of ferroptosis [ 54 , 55 ], staining by IHC, again most evident at 7 dpi ( Fig. 6 D).…”
Section: Resultsmentioning
confidence: 68%
“…5C, D). To further support these findings, we stained hamster lung tissue sections and observe positive TUNEL staining, consistent with apoptosis, with peak at 7 dpi and increased TFRC (Transferrin Receptor Protein 1), a specific marker of ferroptosis [ 54 , 55 ], staining by IHC, again most evident at 7 dpi ( Fig. 6 D).…”
Section: Resultsmentioning
confidence: 68%
“… 39 Upregulation of TRFC promoted ferroptosis by increasing the intracellular iron load. 40 RRM2, JUN, and TP63 were found to increase cellular resistance against ferroptosis by regulating the synthesis, utilization, and regeneration of glutathione. 41 , 42 , 43 A previous study indicated that overexpression of ENPP2 could inhibit erastin‐induced ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The N-myc protein encoded by MYCN gene is an important transcription factor, which can regulate the expression of a variety of target genes and thus participate in a variety of cell biological functions and signaling pathways. 33 , 34 Studies have shown that MYCN can directly target cell cycle-related genes, reduce G1 phase arrest, promote cell into S phase and promote cell proliferation. 33 , 35 The abnormal expression of MYCN was found in neurogenic tumors, including neuroblastoma, neuroendocrine prostate cancer and small cell lung cancer.…”
Section: Discussionmentioning
confidence: 99%